Detensi Imigrasi Berkepanjangan yang Bertentangan dengan HAM pada Fasilitas Detensi Imigrasi di Jepang: Tinjauan Perspektif Institusional - Sari Anggaini; Kurniawaty Iskandar (Badan Penelitian dan Pengembangan Hukum dan HAM, 2022)
Recently, some cases of human rights violations in immigration detention centers across Japan have attracted worldwide attention. Those inhumanely considered cases necessitated the United Nations expressing an opinion through the United Nations Working Group on Arbitrary Detention. This study found that ingrained ideologies of homogeneity in Japanese society give rise to immigration policies that tend to hinder the integration of immigrants into Japanese society. This research looks at three main areas: first, how the ideology of homogeneity led to prolonged immigration detention in Japan; second, whether immigration detention in Japan violates international human rights law; and, finally, the guarantee of human rights protection for detainees in Japan. a qualitative research method using a literature review to describe how ethnic homogeneity causes prolonged immigration detention in Japan that is against international law through an institutional frame.